The effect of molding water content on the hydraulic erosion potential of cohesive soils - Tsai, Wan-Lain (Kansas State University, 1981)
This study was undertaken to gain a better understanding of the erosional characteristics of cohesive soils and to determine the relationship between the amount of erosional loss and the variation in molding water content. Laboratory samples were compacted, saturated, and tested under controlled laboratory conditions using an erosion test apparatus. Erosion tests on both wet and air-dried samples were carried out under the same conditions. It was concluded that the amount of erosional loss is affected by the compacting water content. The soil samples compacted on the wet side of the Standard Proctor optimum water content resulted in a significant reduction in erosional loss of the soil when compared to the same dry density compacted dry of optimum. The test results clearly show that the amount of erosional loss was dependent upon the initial compaction water content and independent of any change in water content after compaction prior to testing. Data also indicated that the critical hydraulic tractive stress for a cohesive soil is significantly affected by changes in the molding water content.
Keywords: Soil erosion; Compacting; Hydraulics